2014
DOI: 10.1038/ki.2013.363
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IGFBP-7 by urinary proteomics as a novel prognostic marker in early acute kidney injury

Abstract: Early diagnosis of acute kidney injury (AKI) and accurate prognostic stratification is a prerequisite for optimal medical management. To identify novel prognostic markers of AKI, urine was collected on the first day of AKI in critically ill patients. Twelve patients with early recovery and 12 matching patients with late/non-recovery were selected and their proteome analyzed by gel electrophoresis and mass spectrometry. We identified eight prognostic candidates including α-1 microglobulin, α-1 antitrypsin, apol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 56 publications
2
74
0
3
Order By: Relevance
“…The median (interquartile range) time from ICU arrival to collection of the first samples was 16 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) hours. At least 3 months of follow-up data were available for 639 (92.3%) patients, and full 9-month outcome was known for 552 (79.8% of the initial cohort) patients, with 217 (39.3% of those with complete follow-up) patients meeting the primary end point of death or dialysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median (interquartile range) time from ICU arrival to collection of the first samples was 16 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) hours. At least 3 months of follow-up data were available for 639 (92.3%) patients, and full 9-month outcome was known for 552 (79.8% of the initial cohort) patients, with 217 (39.3% of those with complete follow-up) patients meeting the primary end point of death or dialysis.…”
Section: Resultsmentioning
confidence: 99%
“…After removing those with in-hospital RRT, [TIMP-2]z[IGFBP7].2.0 remained significantly associated with an increased risk of adverse patient outcomes (9 months; log-rank P,0.001). 12 recently showed that IGFBP7 levels predicted mortality, renal recovery, and severity/duration of AKI in a smaller cohort of critically ill adults. These biomarkers have been shown to be involved in a diverse array of biologic processes, including apoptosis/cellular senescence, [13][14][15] inflammation, 16 tubular regeneration, 17 and cell cycle arrest.…”
Section: Risk Of Death or Dialysis Increased Atmentioning
confidence: 99%
“…Other studies show that urine NGAL can predict renal outcome and mortality in patients with cirrhosis and associated bacterial infections [24], serve as a prognostic biomarker for AKI in hospitalized cirrhotic patients with AKI-prone conditions [13], and predict the severity of contrast-induced AKI in CKD patients undergoing coronary procedures [25]. Nevertheless, in a study which compared urine biomarkers, it was observed that urine IGFBP-7 was a more reliable predictor of renal outcome (renal recovery and AKI severity) than NGAL [26]. The former is a promising novel prognostic biomarker which still requires further evaluation.…”
Section: Literature Search Strategymentioning
confidence: 99%
“…The above-stated conditions appear to be the most relevant in the development of tubular cell injury, when the loss of cell polarity, brush border derangement, and cell sloughing might occur. Such injury may deflect the organism from normal repair toward maladaptive and lead to CKD, which further predisposes the individual to recurrent AKI [24].…”
Section: Biomarkersmentioning
confidence: 99%